Efektivitas Kombinasi Pijat Endorphin dan Aroma Terapi Rose terhadap Pengurangan Nyeri pada Persalinan Kala I di Puskesmas Pahandut Kota Palangka Raya - Lensi Natalia Tambunan; Dewi Aprilianti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The physiological condition experienced by all maternity mothers is labor pain. It is caused by ischemic u muscles, withdrawal and traction of the uteri ligament, ovarian traction, fallopian tubes, and distension of the lower part of the uteri, pelvic floor muscles, and perineum. How to reduce pain with non-pharmacological treatment namely endorphin massage (Endorphine Massage) and aromatherapy rose administration. Aromatherapy is a method that uses essential oils that can improve physical health and also improve emotional health. The aroma of essential oils can provide calmness and can reduce pain in childbirth. Rose or rose atrisi oil referred to as the queen of oils has a delicious aroma, stimulates feelings of comfort, and reduces pain. This study used a sample of 30 maternity respondents who came to the maternity room of Pahandut Puskesmas Palangka Raya city which numbered 30 respondents. In this study as a variable independent is the intervention of Endorphin Massage and aromatherapy rose, while as a variable dependent is a pain. In this study, we used statistical T-Test using computerization. From the results of the study, it can be known that the mean rank of pain in the maternity mother is not given endorphin massage and aromatherapy rose is greater than the pain in the maternity mother given endorphin massage and aromatherapy rose, and obtained a p-value of 0.00, so it can be concluded that there is a significant difference in labor pain in times I without endorphin massage and rose therapy with endorphin massage and aromatherapy rose.